Lean Construction Tools - Ansah, Richard Hannis; Sorooshian, Shahryar; Shariman, Mustafa; Duvvuru, Gomanth (IEOM Society International, 2016)
Production management is at the center of lean construction ( LC ) and keeps running from the project initiation through project handover to maintenance. Several powerful lean production techniques and tools have been developed over the past decade to manage construction projects. Some of these are procedural, some are c onceptual, and some are embedded in programming. Besides, w hile some of these tools are simple, complexities revolves around others, for instance, the last planner system (LPS) is considered complex. This different set of tools is very effective in the han ds of managers stimulated by the lean project conceptualizatio n and management. It has been indicated that Danish contractors had increased productivity by 20%, minimized project duration by 10%, expanded efficiency by 20%, and enhanced profitability 20% - 40% on projects where lean principles are adopted. However, no list would be conclusive and accurate for long because innovation is in progress and new techniques and tools emerge constantly. In this study, we identify suitable lean construction tools based on their applicability and ability to control delays in Malaysian construction projects . This study provides construction managements with suitable lean construction tools to build a realistic and r ational lean appli cation guide.